PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK DENGN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Keisha Angeli Diva Miracle; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of profitability and leverage on tax avoidance, with good corporate governance (GCG) as a moderating variable. This study uses data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The research applies a quantitative approach by analyzing secondary data from 87 manufacturing companies selected through purposive sampling based on specific criteria. Data analysis was conducted using multiple linear regression and moderated regression analysis.The results indicate that profitability has a negative effect on tax avoidance, while leverage has a positive effect. Good corporate governance strengthens the relationship between profitability and tax avoidance, but weakens the relationship between leverage and tax avoidance.